Computer-Implemented Inventions and Computer Programs – Status Quo in Slovenia and EU (Informatica, 2021)
In Slovenia, there is no legal basis for computer-implemented inventions, and in the European Union (EU) such inventions are not yet clearly defined. Over the last twenty years there have been many heated debates in the EU arena concerning a single legal instrument, but a final solution remains elusive. In Slovenia and the EU, legal protection of computer-implemented inventions thus remains on thin ice: there are certain non-obvious combinations for obtaining a patent, but ultimately the decisive factor may as well be how the patent application is written. This status quo therefore necessitates an examination of this field: to arrive at a legal basis that would regulate the patenting of computer-implemented inventions it is necessary to identify and address the most critical points. This paper deals with this issue. It starts by presenting examples of computer-implemented inventions, followed by an overview of the state of play – the status quo concerning legal protection in Slovenia and the EU. This paper also provides an overview of copyright as a legal basis for computer programs, which is the same in Slovenia and in the EU. Copyright is not exclusive, as computer programs are often also protected as trade secrets and as know-how.